Barriers and strategies needed to improve maternal health services among pregnant adolescents in Uganda: a qualitative study - Samuel Nambile Cumber; Catherine Atuhaire; Vivian Namuli; Malin Bogren; Helen Elden (Taylor & Francis Group, 2022)
Background In Uganda, the uptake of maternal health services is very low, with only 41.1% of pregnant adolescent girls attending the eight antenatal visits that are recommended by the World Health Organisation. Uptake of maternal health services is essential in reducing the current level of adolescent pregnancies as well as its adverse effects on adolescent mothers and their babies, such as preterm deliveries, prolonged labour, death during pregnancy, and childbirth. No previous study has described pregnant adolescents' experiences with maternal health services in Uganda. Objective This study aimed to describe the barriers and strategies needed to improve maternal health services among pregnant adolescents in Uganda. Methods Data were collected in the Naguru Teenage Information and Health Centre in Uganda through individual interviews involving 31 pregnant adolescents. The transcribed interviews were inductively analysed through content analysis. Results The pregnant adolescents described difficulty in reaching, as well as lack of financial support to visit, the Naguru Teenage Information and Health Centre, which is a clinic providing youth friendly services. Feelings of being discriminated against and disrespected by health workers, and lack of privacy when receiving health services was major barriers that hindered their access to maternal health services. Pregnant adolescents' access to these services can be enhanced by improving health workers' working conditions, accelerating community and health worker awareness on ways to mitigate these barriers, and developing policies that encourage men's involvement in maternal health services. Conclusion Adolescents in Uganda face considerable barriers to accessing improved and quality maternal health services. To mitigate these barriers, according to the adolescents, considerable efforts are required to tackle health workers' working conditions and sensitise the community on the importance of, as well as securing the availability of, maternal health services for pregnant adolescents. Future research should focus on pregnant adolescents who receive family support.